Triumf i porazka myrnoho rozmai͏̈ttja = Triumph and defeat of peaceful diversity - Smytsnyuk, Pavlo (Bogoslovs'ki rozdymi, 2020)
Book review:Oleg Davydov. Otkrovenie liubvi. Trinitarnaia istina bytiia. Seriia Sovremennoe bogoslovie [Revelation of Love. The TrinitarianTruth of Being]. Moscow: BBI, 2020. xxxviii + 658. ISBN 9785896473909; 891.00 RUB